2019
DOI: 10.1016/j.hjc.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral paricalcitol therapy on arterial stiffness and osteopontin in hypertensive patients with chronic kidney disease and secondary hyperparathyroidism

Abstract: Treatment with oral paricalcitol in hypertensive subjects suffering from CKD stages 3-5 and secondary hyperparathyroidism is accompanied by amelioration of arterial stiffness as reflected by the reduction of carotid-femoral PWV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The effect of vitamin D supplementation on diastolic BP was also described in five trials . The pooled analysis showed that diastolic BP had no difference between the vitamin D intervention and control groups (SMD, 0.01; 95% CI, −0.26 to 0.27; P = 0.97; Figure ).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The effect of vitamin D supplementation on diastolic BP was also described in five trials . The pooled analysis showed that diastolic BP had no difference between the vitamin D intervention and control groups (SMD, 0.01; 95% CI, −0.26 to 0.27; P = 0.97; Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…Six studies described the changes in systolic BP . The results of the pooled analysis demonstrated that systolic BP was not different in the group receiving vitamin D compared with the control group (SMD, −0.04; 95% CI, −0.29 to 0.22; P = 0.77; Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, paricalcitol have a therapeutic advantage compared to calcitriol that is consistent with the suppression of renin production (reduced side effects of hypercalcemia) and lack of vascular calcium deposition, which instead causes aortic calcifications with arterial stiffness and hypertension regardless of plasma Ca and P levels. The reason for the selective effect of paricalcitol has to be better elucidated since its clearance from the bloodstream is comparable to that of 1,25(OH)2D [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Vitamin D Its Analogs and Cardiovascular Disordersmentioning
confidence: 99%